An Improved Centralized Cognitive Radio Network Spectrum Allocation Algorithm Based on the Allocation Sequence - Jianli Zhao; Jinsha Yuan (International Journal of Distributed Sensor Networks)
The demand of the wireless communications service is increasing in recent years, and the demand of the wireless communication rate is increasing too. However, the static spectrum allocation mechanism results in lots of free spectrum resources in space, and the spectrum is wasted. The cognitive radio technology with intelligent searching and efficient utilization of the idle spectrum resources just provides the opportunity to use the free spectrum resources. Thus, the spectrum allocation technology of the cognitive radio has also been more and more broadly concerned. In order to avoid the interference, a mathematical model of spectrum allocation for cognitive radio spectrum allocation algorithm is established through a graph theory. The spectrum allocation algorithms with different allocation objectives based on graph theory are studied according to the different network structures. After the basic ideas and allocation processes of these algorithms are described, a centralized network spectrum allocation algorithm based on the allocation sequence is proposed. Simulation results show that the improved algorithm can significantly reduce the time overhead and can have better fairness compared with other existing Collaborative-Max-Sum-Reward (CSUM), Collaborative-Max-Min-Reward (CMIN), and Collaborative-Max-Proportional-Fair (CFAIR) algorithms under the same design criterion.